Dalcroze Application: Early Childhood Music and Movement Activities to Develop Rhythmic Senses - Eungamporn, Nillawanna (Rangsit Music Journal, 2020)
The aim of this study is to create examples of music and movement activities for early childhood based on the philosophy of Emile Jaques-Dalcroze. Many contemporary researchers had affirmed that music is the most significant impact in fostering the child development of the first six years. “Rhythm” is the most appealing element of music to every child. The set of 5 inspiring piano pieces are carefully chosen to inspire the series of rhythmic exercises for early childhood music classes. These series of music and movement activities are excellent examples and tools for early childhood teachers to build the solid music foundation for young children.